Doping method defect passivation perovskite solar cell and preparation method thereof
By doping organic acid salts, the defects in perovskite solar cells are passivated, and the lattice mismatch and energy level mismatch between SnO2 and perovskite are solved, which significantly improves the photoelectric conversion efficiency and device stability of perovskite solar cells.
Patent Information
- Application Number
- CN202411752777.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-18
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
Existing planar positive perovskite solar cells are prone to defects such as vacancy, gap and inverse position, resulting in shallow energy level defects and hindering the extraction and transmission of charges. There is a problem of lattice mismatch and energy level mismatch between SnO2 and perovskites.
By doping organic acid salts with SnO2 and perovskite materials, the passivation of amino and carboxyl groups is used to reduce defects in SnO2 and perovskite films, and the quality of the electron transport layer and the perovskite absorption layer is improved.
It effectively improves the photoelectric conversion efficiency of perovskite solar cells, with the open circuit voltage increased by 0.06V, the filling factor increased by 3.75%, the photoelectric conversion efficiency increased by 12.4%, and suppresses the hysteresis effect of solar cells.
Smart Images

Figure CN119604171A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cell preparation, and in particular to a doping defect passivation perovskite solar cell and a preparation method thereof. Background Art
[0002] Perovskite solar cells have attracted extensive attention from scholars at home and abroad in recent years due to their low cost, abundant raw materials, simple preparation process and flexible preparation. Perovskite materials have an ABX3 structure, and the A-site ion is usually a formamidine ion (FA + ), methylamine ion (Methylamine, MA + ) or cesium ion (Cs + ) etc.; B-site ions are usually divalent metal ions such as lead ions and tin ions; X is usually halogen ions such as iodine ions, bromide ions, or chloride ions. Compared with the indirect bandgap material crystalline silicon, perovskite is a direct bandgap semiconductor material with adjustable composition, which has less phonon absorption and high light absorption coefficient (10 5 cm -1 ), large carrier diffusion distance (>1μm), small exciton binding energy (~50meV), high carrier mobility (100cm 2 V -1 s -1 ) and high defect tolerance, so the photoelectric conversion efficiency of perovskite solar cells has rapidly increased from 3.8% in 2009 to 26.7% today. At present, the commonly used perovskite solar cell device structure is a planar positive type, usually composed of five parts: conductive glass substrate (ITO, FTO, etc.), electron transport layer (SnO2, TiO2, etc.), perovskite layer, hole transport layer (Spiro-OMeTAD, PTAA, P3HT, etc.), and electrode (Ag, Au).
[0003] Planar positive perovskite solar cells still have some shortcomings: (1) During the annealing process, the SnO2 electron transport layer is prone to form vacancies (V O 、V Sn ), gap (O i , Sn i ), anti-site (SnO, OSn) and other defects. (2) Perovskite materials are organic-inorganic hybrid materials, which are very easy to form shallow energy level defects during spin coating and annealing, such as uncoordinated Pb 2+ , Pb-I antisite, metallic lead clusters, I -Vacancy and other defects. These defects will form charge recombination centers, hindering the extraction and transfer of charges. (3) There are problems such as lattice mismatch and energy level mismatch between SnO2 and perovskite, which affect the further improvement of efficiency. Therefore, the preparation of high-quality SnO2 and perovskite films is an important means to further improve the photoelectric conversion efficiency of perovskite solar cells, which is conducive to the synergistic improvement of the performance and stability of perovskite solar cells. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a doping method defect passivation perovskite solar cell and a preparation method thereof, so as to solve the problems that the existing planar positive perovskite solar cells are prone to form defects such as vacancies, gaps and anti-sites, are prone to produce shallow energy level defects, hinder the extraction and transmission of charges, and have lattice mismatch and energy level mismatch between SnO2 and perovskite.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] A method for preparing a defect-passivated perovskite solar cell by doping method comprises the following steps:
[0007] (1) mixing an organic acid salt solution and a SnO2 aqueous solution and then sonicating to obtain an electron transport layer precursor solution;
[0008] (2) preparing a halogen compound solution as a perovskite precursor solution I, and preparing an organic salt solution as a perovskite precursor solution II;
[0009] (3) Fk209, tributyl phosphate, lithium salt solution, Spiro-OMeTAD and chlorobenzene are mixed evenly, or tributyl phosphate, lithium salt solution, P3HT and chlorobenzene are mixed evenly to obtain a hole transport layer precursor solution;
[0010] (4) On the substrate material, the electron transport layer precursor solution obtained in step (1), the perovskite precursor solutions I and II obtained in step (2), and the hole transport layer precursor solution obtained in step (3) are sequentially spin-coated to prepare a SnO2 electron transport layer, a perovskite absorption layer, and a hole transport layer; after oxidation, a molybdenum oxide layer and a silver electrode are prepared on the hole transport layer to obtain a SnO2 electron transport layer.
[0011] Furthermore, in step (1), the organic acid salt comprises any one of formamidine formate, formamidine acetate, 3-(methylamino)propionic acid, isonicotinic acid and 3-azetidine carboxylic acid; the solvent of the organic acid salt solution is water, and the concentration is 10-22 mg / mL.
[0012] Preferably, the solvent of the organic acid salt solution is water, and the concentration is 20 mg / mL.
[0013] Furthermore, in step (1), the mass concentration of the SnO2 aqueous solution is 1-5%; the volume ratio of the organic acid salt solution to the SnO2 aqueous solution is 0.5-2:15-25.
[0014] The beneficial effects of adopting the above further technical solution are:
[0015] The present invention adopts a method of doping SnO2 with organic acid salts, and uses amino and carboxyl groups in the organic acid salts to play a passivation role, thereby preparing high-quality SnO2 and perovskite films, effectively improving the efficiency of perovskite solar cells, and improving the electron transmission capacity of the electron transport layer by doping with organic acid salts, thereby effectively improving the carrier extraction capacity, and further improving the photoelectric conversion efficiency of the device. After doping with SnO2, the open circuit voltage of the perovskite solar cell is increased from the original 1.06V to 1.12V; the fill factor is increased from 75.23% to 78.98%, and the photoelectric conversion efficiency is increased from the initial 19.07% to 21.43%, which is a relative increase of 12.4%.
[0016] Furthermore, in step (2), the halogen-containing compound is lead iodide or a mixture of lead iodide and cesium iodide; the solvent of the halogen-containing compound solution is a mixed solvent of DMF and DMSO, the concentration of lead iodide is 600-700 mg / mL, and the concentration of cesium iodide is 0-25 mg / mL; the organic salt is a mixture of iodomethylformamidine and chloromethylamine, or a mixture of iodomethylformamidine, chloromethylamine, and iodomethylamine; and the solvent of the organic salt solution is isopropanol.
[0017] Preferably, the halogen compound solution is a lead iodide solution with a concentration of 692 mg / mL or a mixed solution of lead iodide with a concentration of 742.2 mg / mL and cesium iodide with a concentration of 19.8 mg / mL, and the solvent is a mixed solvent of DMF and DMSO with a volume ratio of 9:1;
[0018] The organic salt solution is a mixed solution of 90 mg / mL iodomethylformamidine, 9 mg / mL chloromethylamine and 6.39 mg / mL iodomethylamine, and the solvent is isopropanol; or a mixed solution of 90 mg / mL iodomethylformamidine and 18 mg / mL chloromethylamine, and the solvent is isopropanol.
[0019] Furthermore, in step (3), the mass volume ratio of Spiro-OMeTAD, Fk209, tributyl phosphate, lithium salt solution and chlorobenzene is 65-80 mg: 5-15 mg: 20-40 μL: 25-45 μL: 0.5-2 mL; the mass volume ratio of P3HT, tributyl phosphate, lithium salt solution and chlorobenzene is 10-20 mg: 20-40 μL: 25-45 μL: 0.5-2 mL.
[0020] Preferably, in step (3), the mass volume ratio of Spiro-OMeTAD, Fk209, tributyl phosphate, lithium salt solution and chlorobenzene is 72.3 mg: 9 mg: 30 μL: 35 μL: 1 mL; the mass volume ratio of P3HT, tributyl phosphate, lithium salt solution and chlorobenzene is 15 mg: 30 μL: 35 μL: 1 mL.
[0021] Furthermore, the lithium salt solutions are all acetonitrile solutions of lithium bis(trifluoromethanesulfonyl)imide with a concentration of 200-300 mg / mL.
[0022] Preferably, the lithium salt solution is an acetonitrile solution of lithium bis(trifluoromethanesulfonyl)imide with a concentration of 200-300 mg / mL.
[0023] Furthermore, in step (4), the substrate material is ITO transparent conductive glass, which is subjected to ozone treatment for 10-40 minutes before spin coating.
[0024] Furthermore, in step (4), the spin coating speed of the SnO2 electron transport layer is 3000-6000 rpm, the spin coating time is 10-60s, and the coating is annealed at 90-170°C for 15-45min; in the perovskite absorption layer, the spin coating speed of the perovskite absorption layer precursor solution I is 1000-2000 rpm, the spin coating time is 10-60s, and the coating is annealed at 50-90°C for 0.5-5min after spin coating, the spin coating speed of the perovskite absorption layer precursor solution II is 1500-3000 rpm, the spin coating time is 10-60s, and the coating is annealed at 100-150°C for 10-30min after spin coating; the spin coating speed of the hole transport layer is 1500-5000 rpm, the spin coating time is 10-60s; and the oxidation time is 1-15 hours.
[0025] The beneficial effect of adopting the above-mentioned further technical scheme is as follows: the present invention generates a perovskite absorption layer by first spin-coating a precursor solution containing lead iodide and then spin-coating an organic salt solution, wherein FAI is the main component of the organic salt, and MACl and MAI assist the perovskite crystallization in the annealing stage, thereby effectively realizing the passivation of defects and solving the problem that shallow energy level defects are easily formed when preparing perovskite materials in the prior art.
[0026] Furthermore, in step (4), the thickness of the SnO2 electron transport layer is 20-100nm; the thickness of the perovskite absorption layer is 500-1000nm; the thickness of the hole transport layer is 150-300nm; the thickness of the molybdenum oxide layer is 10-20nm; and the thickness of the silver electrode is 100-200nm.
[0027] Preferably, the thickness of the silver electrode is 140 nm.
[0028] A doping defect-passivated perovskite solar cell is prepared by the above preparation method.
[0029] The present invention has the following beneficial effects:
[0030] The present invention provides a method for improving the performance of perovskite solar cells by defect passivation through doping, which effectively solves the problem that there are a large number of defects in the existing methods for preparing SnO2 and perovskite films. The organic acid salt containing both amino and carboxyl groups is doped with SnO2, and the nitrogen and oxygen in the amino and carboxyl groups are reacted with the Sn in SnO2. 4+ , oxygen vacancies, and passivation of uncoordinated Pb in perovskite 2+ , halogen vacancies and other defects, thereby passivating a large number of defect structures in SnO2 and perovskite films, reducing the non-radiative recombination of the device, and improving the carrier transmission capacity, thereby effectively suppressing the hysteresis effect of solar cells and improving the photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of the structure of a defect-passivated perovskite solar cell prepared by a doping method according to an embodiment of the present invention;
[0032] Figure 2 This is a schematic diagram of the structure of a perovskite solar cell obtained in a comparative example of the present invention;
[0033] Figure 3 It is the JV curve diagram of the battery in the test example. DETAILED DESCRIPTION
[0034] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0035] Embodiment 1:
[0036] A method for preparing a defect-passivated perovskite solar cell by doping method comprises the following steps:
[0037] (1) Preparation of SnO2 electron transport layer
[0038] ① Preparation of organic acid salt-doped SnO2 precursor solution: first dilute the 12% by mass SnO2 aqueous solution colloid with deionized water to one-fourth of the original; then dissolve 20 mg of formamidine formate (FAHCOO) in 1 mL of water to obtain FAHCOO solution; finally, add 5 μL of FAHCOO solution to 100 μL of the diluted SnO2 aqueous solution to obtain an electron transport layer precursor solution.
[0039] ② Pretreatment of substrate materials: The ITO transparent conductive glass was ultrasonically cleaned with cleaning solution, deionized water, acetone and isopropanol for 40 minutes each, dried with nitrogen and placed in a UV ozone machine for UV ozone treatment for 20 minutes.
[0040] ③SnO2 electron transport layer processing: first, the surface of the pre-treated ITO transparent conductive glass was spin-coated with a SnO2 precursor solution doped with FAHCOO at a speed of 5000 rpm for 30 seconds, and then annealed on a 150°C hot plate for 30 minutes at an ambient temperature of 27°C and a humidity of 30%. Finally, the annealed material was treated with UV ozone for 10 minutes and then moved into a glove box to obtain a SnO2 electron transport layer.
[0041] (2) Preparation of perovskite absorption layer
[0042] ① Preparation of halogen compound solution: prepare a lead iodide solution with a concentration of 692 mg / mL, the solvent is a mixed solvent of DMF and DMSO with a volume ratio of 9:1, and stir with a magnetic stirrer for 2 hours after mixing.
[0043] ② Preparation of a mixed solution of FAI, MACl and MAI: Dissolve 90 mg of iodomethylformamidine (FAI), 9 mg of chloromethylamine (MACl) and 6.39 mg of iodomethylamine (MAI) in 1 mL of isopropanol and stir with a magnetic stirrer for 1 h.
[0044] ③ Preparation of perovskite absorption layer: Take 40μL of lead iodide solution and spin-coat it on the SnO2 electron transport layer. The spin-coating conditions are: rotation speed 1500rpm, time 30s; anneal in the glove box after spin coating, annealing temperature is 70℃, annealing time is 1min; then spin-coat 40μL of FAI, MACl and MAI mixed solution on the annealed lead iodide film, spin coating conditions are: rotation speed 2300rpm, time 30s; anneal in air, annealing temperature is 125℃, time is 15min, annealing environment humidity is 35%, to obtain the perovskite absorption layer.
[0045] (3) Preparation of hole transport layer
[0046] ① Preparation of hole transport layer Spiro-OMeTAD precursor solution: 72.3 mg of 2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (Spiro-OMeTAD), 9 mg of tri[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt tri(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide) (Fk209), 30 μL of tributyl phosphate (tBP), 35 μL of lithium salt solution and 1 mL of chlorobenzene were mixed evenly to obtain a solution; wherein, the lithium salt solution was prepared by dissolving 260 mg of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) in 1 mL of acetonitrile.
[0047] ② Preparation of hole transport layer: Take 40 μL of hole transport layer Spiro-OMeTAD precursor solution and spin coat it on the perovskite absorption layer at a spin coating speed of 3000 rpm for 30 seconds, then place it in a drying cabinet at 26°C and 1% humidity and dry it for 2 hours.
[0048] (4) Vacuum deposition electrode
[0049] First, a molybdenum oxide layer was deposited on the hole transport layer by vacuum evaporation with a vacuum degree of 10 -5 Pa, the evaporation rate was 0.05 nm / s, the total evaporation thickness was 20 nm, and a molybdenum oxide layer was obtained.
[0050] Then, the metal electrode Ag is deposited on the molybdenum oxide layer by vacuum evaporation, and the vacuum degree is 1.4×10 -4 Pa, evaporation rate of 0.15nm / s, total evaporation thickness of 140nm, the defect passivation perovskite solar cell with doping method was prepared. The structural diagram is shown in Figure 1 shown.
[0051] Embodiment 2:
[0052] A method for preparing a defect-passivated perovskite solar cell by doping method comprises the following steps:
[0053] The preparation method is the same as that of Example 1, except that the volume of the FAHCOO solution in the electron transport layer precursor solution in step (1) is changed to 10 μL.
[0054] Embodiment 3:
[0055] A method for preparing a defect-passivated perovskite solar cell by doping method comprises the following steps:
[0056] The preparation method is the same as that in Example 1, except that the FAHCOO solution in step (1) is replaced by an aqueous solution of formamidine acetate having a concentration of 20 mg / mL; the mixed solution of FAI, MACl and MAI in step (2) is replaced by a mixed solution of FAI and MACl, and the preparation method of the mixed solution of FAI and MACl is as follows: 90 mg of iodomethyl formamidine (FAI) and 18 mg of chloromethylamine (MACl) are dissolved in 1 mL of isopropanol and stirred with a magnetic stirrer for 1 h; the hole transport layer Spiro-OMeTAD precursor solution in step (3) is replaced by a hole transport layer P3HT precursor solution, and the preparation method of the hole transport layer P3HT precursor solution is as follows: 15 mg of [poly (3-hexylthiophenol)] (P3HT), 30 μL of tributyl phosphate (tBP), 35 μL of lithium salt solution and 1 mL of chlorobenzene are mixed evenly, and the preparation method of the lithium salt is the same as that in Example 1.
[0057] Embodiment 4:
[0058] A method for preparing a defect-passivated perovskite solar cell by doping method comprises the following steps:
[0059] The preparation method is the same as that of Example 1, except that the formamidine formate solution in step (1) is replaced by an aqueous solution of isonicotinic acid with a concentration of 20 mg / mL; the halogen-containing compound solution in step (2) is replaced by a mixed solution of lead iodide with a concentration of 742.2 mg / mL and cesium iodide with a concentration of 19.8 mg / mL, and the solvent is a mixed solvent of DMF and DMSO with a volume ratio of 9:1.
[0060] Comparative Example 1:
[0061] A method for preparing a perovskite solar cell comprises the following steps:
[0062] The preparation method is the same as that of Example 1, except that in step (1), when preparing the SnO2 electron transport layer, the diluted tin oxide solution is directly used as the electron transport layer precursor solution to prepare a perovskite solar cell. The structural diagram is shown in FIG. Figure 2 shown.
[0063] Test example:
[0064] The perovskite solar cells prepared in Example 1 and Comparative Example 1 were analyzed and tested using a solar simulator produced by Zhuoli Hanguang. The light source was a 500W xenon lamp. The incident light was calibrated using a KG-5 standard silicon cell. The light intensity incident on the cell during the test was kept at a standard sunlight intensity (AM1.5 G, 100mW / cm 2 ) intensity. Voltage was applied to both ends of the battery. The voltage applied during forward scanning was 0-1.2V, and the voltage applied during reverse scanning was 1.2-0V. The current was collected by Keithley 2400, and the JV curve of the battery was finally obtained.
[0065] The experimental results are as follows Figure 3 As shown, compared with Comparative Example 1, the open circuit voltage of the perovskite solar cell prepared in Example 1 is increased from the original 1.06V to 1.12V; the fill factor is increased from 75.23% to 78.98%, and the photoelectric conversion efficiency is increased from the initial 19.07% to 21.43%, a relative increase of 12.4%. In order to obtain a universal conclusion, the photoelectric conversion efficiency of the perovskite solar cells obtained from multiple experiments was statistically analyzed. The statistical results show that compared with Comparative Example 1, the photoelectric conversion efficiency of Example 1 is effectively improved. By comparing the photoelectric performance parameters of the device, it is found that the improvement in photoelectric conversion efficiency is attributed to the improvement of open circuit voltage and fill factor. This is because doping effectively passivates defects in the device, reduces non-radiative recombination of the device, and improves the carrier transmission capacity. At the same time, the hysteresis effect of the perovskite solar cell is also significantly suppressed.
[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a defect-passivated perovskite solar cell by doping, characterized in that: The following steps are involved: (1) mixing an organic acid salt solution and a SnO2 aqueous solution and then sonicating to obtain an electron transport layer precursor solution; (2) preparing a halogen compound solution as a perovskite precursor solution I, and preparing an organic salt solution as a perovskite precursor solution II; (3) Fk209, tributyl phosphate, lithium salt solution, Spiro-OMeTAD and chlorobenzene are mixed evenly, or tributyl phosphate, lithium salt solution, P3HT and chlorobenzene are mixed evenly to obtain a hole transport layer precursor solution; (4) On the substrate material, the electron transport layer precursor solution obtained in step (1), the perovskite precursor solutions I and II obtained in step (2), and the hole transport layer precursor solution obtained in step (3) are sequentially spin-coated to prepare a SnO2 electron transport layer, a perovskite absorption layer, and a hole transport layer; after oxidation, a molybdenum oxide layer and a silver electrode are prepared on the hole transport layer to obtain a SnO2 electron transport layer.
2. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 1, characterized in that: The organic acid salt in step (1) includes any one of formamidine formate, formamidine acetate, 3-(methylamino)propionic acid, isonicotinic acid and 3-azetidine carboxylic acid; the solvent of the organic acid salt solution is water, and the concentration is 10-22 mg / mL.
3. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 1, characterized in that: The mass concentration of the SnO2 aqueous solution in step (1) is 1-5%; the volume ratio of the organic acid salt solution to the SnO2 aqueous solution is 0.5-2:15-25.
4. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 1, characterized in that: In the step (2), the halogen-containing compound is lead iodide or a mixture of lead iodide and cesium iodide; the solvent of the halogen-containing compound solution is a mixed solvent of DMF and DMSO, the concentration of lead iodide is 600-700 mg / mL, and the concentration of cesium iodide is 0-25 mg / mL; the organic salt is a mixture of iodomethylformamidine and chloromethylamine, or a mixture of iodomethylformamidine, chloromethylamine, and iodomethylamine; and the solvent of the organic salt solution is isopropanol.
5. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 1, characterized in that: In the step (3), the mass volume ratio of Spiro-OMeTAD, Fk209, tributyl phosphate, lithium salt solution and chlorobenzene is 65-80 mg: 5-15 mg: 20-40 μL: 25-45 μL: 0.5-2 mL; the mass volume ratio of P3HT, tributyl phosphate, lithium salt solution and chlorobenzene is 10-20 mg: 20-40 μL: 25-45 μL: 0.5-2 mL.
6. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 5, characterized in that: The lithium salt solutions are all acetonitrile solutions of lithium bis(trifluoromethanesulfonyl)imide with a concentration of 200-300 mg / mL.
7. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 1, characterized in that: In the step (4), the substrate material is ITO transparent conductive glass, which is subjected to ozone treatment for 10-40 minutes before spin coating.
8. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 1, characterized in that: In the step (4), the spin coating speed of the SnO2 electron transport layer is 3000-6000 rpm, the spin coating time is 10-60s, and the coating is annealed at 90-170°C for 15-45min; in the perovskite absorption layer, the spin coating speed of the perovskite absorption layer precursor solution I is 1000-2000 rpm, the spin coating time is 10-60s, and the coating is annealed at 50-90°C for 0.5-5min, the spin coating speed of the perovskite absorption layer precursor solution II is 1500-3000 rpm, the spin coating time is 10-60s, and the coating is annealed at 100-150°C for 10-30min; the spin coating speed of the hole transport layer is 1500-5000 rpm, the spin coating time is 10-60s; and the oxidation time is 1-15 hours.
9. The method for preparing a defect-passivated perovskite solar cell by doping method according to claim 1, characterized in that: In the step (4), the thickness of the SnO2 electron transport layer is 20-100nm; the thickness of the perovskite absorption layer is 500-1000nm; the thickness of the hole transport layer is 150-300nm; the thickness of the molybdenum oxide layer is 10-20nm; and the thickness of the silver electrode is 100-200nm.
10. A doping method defect passivation perovskite solar cell, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Perovskite solar cell with EDTA-2Na modified electron transport layer and preparation method of perovskite solar cell
CN115768143A
Slurry composition and preparation method thereof, electron transport film layer and preparation method thereof, perovskite solar cell and preparation method thereof
CN116634781A
Solar cell
US20230105166A1
Electron transport layer for perovskite solar cell and perovskite solar cell including same
US20240260283A1